Alkali-activated regenerated foam concrete and preparation method thereof
By using alkali-induced regeneration technology and vertical slurry mixing method in the preparation of foam concrete, the problems of high energy consumption and difficulty in cleaning mixing equipment in the existing technology are solved, and the preparation of foam concrete with low density, high strength and low thermal conductivity is achieved.
Patent Information
- Application Number
- CN202211705044.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-12-29
AI Technical Summary
The existing foam concrete preparation methods have problems such as high energy consumption, difficulty in cleaning the mixing equipment, inaccurate measurement of foam dosage, and obvious differences in density and strength.
Alkali-activated regenerated foam concrete technology is adopted, and the mixing effect and quality of the concrete are improved by using a vertical slurry mixing pot and combining manual and mechanical mixing methods. At the same time, the foam is frozen and the water-binder ratio is adjusted to ensure the accuracy of the foam dosage and the efficient use of recycled powder.
It achieves the preparation of foam concrete with low density, high strength and low thermal conductivity, and the mixing equipment is easy to clean. It can efficiently utilize low-quality recycled powder and control the density and strength within an appropriate range.
Smart Images

Figure CN116514496B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to an alkali-activated regenerated foam concrete and a preparation method thereof. Background Art
[0002] Most of the published literature uses industrial solid waste with all components fired at high temperature, which is high-quality and highly active solid waste. The cementitious material does not use cement but water glass, which has high strength but high cost. The density of the prepared foam concrete is mostly 600-800kg / m 3 Most low-density foam concrete below grade 500 is mixed at high temperature and formed at high pressure, which consumes a lot of energy. Density 420kg / m 3 There is a significant difference in the strength of foam concrete when the value is around .
[0003] Patent No. CN113024179A prepared a dry density less than 310kg / m 3 , thermal conductivity less than 0.063W / m·K, compressive strength greater than 0.4MPa foam concrete. However, it needs to be mixed with a horizontal mixer, which is extremely difficult to clean and cannot screen a large number of formulas; CN113149580A uses 30% 0-4.75mm recycled powder, 50% cement, 20% fly ash, aerogel, and vitrified microspheres to prepare a density of 399kg / m 3 Strength 0.9MPa, thermal conductivity 0.094W / (m·K), density 502kg / m 3 Strength 1.2MPa, thermal conductivity 0.130W / (m·K), density 653kg / m 3 Strength 1.7MPa, thermal conductivity 0.122W / (m·K), density 726kg / m 3 Foamed concrete with a strength of 1.9MPa and a thermal conductivity of 0.139W / (m·K). However, it needs to be mixed with a horizontal mixer, which is extremely difficult to clean and cannot screen a large number of formulas. The foam dosage is not accurately measured by the mass of the foaming agent, and foamed concrete of a specified density cannot be prepared. The recycled powder dosage is low.
[0004] Patent No.: CN113429183A Recycled foam concrete density 950-1300kg / m 3 , thermal conductivity 0.291-0.409W / (m·K), compressive strength 2.7-3.8MPa, recycled sand powder content up to 83%, but the density of foamed concrete is relatively high; CN109694207A prepared a density of 255-270kg / m 3The foam concrete has a strength of 0.46-0.70MPa, and the foam is accurately measured. It is recommended to use a 1L plastic beaker to measure, and use a handheld stirrer to stir the cement slurry and mix the foam. However, high-activity solid waste is used. The 7d activity index of silica fume is ≥105%, and the activity indexes of mineral powder, steel slag powder, and fly ash are ≥105%, ≥80%, and ≥70% respectively; the density of the foam concrete made by CN105272043A is 285-324kg / m 3 , strength 1.6-2.7MPa. But the stirring temperature is 50-70 degrees, and the energy consumption is high. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and to provide an alkali-activated regenerated foam concrete and a preparation method thereof.
[0006] In order to achieve the above invention purpose, the technical solution provided by the present invention is as follows:
[0007] The invention discloses an alkali-activated regenerated foam concrete, which comprises cement, recycled powder, an activator, water and foam. The recycled powder is one of recycled micro powder and recycled sand powder, the activator is at least one of sodium carbonate, sodium sulfate and sodium silicate, the cement accounts for 60% of the total mass of cement and recycled powder, the recycled powder accounts for 40% of the total mass of cement and recycled powder, the sodium carbonate accounts for 0-0.5% of the mass of recycled powder, the sodium sulfate accounts for 0-6.36% of the mass of recycled powder, the sodium silicate accounts for 0-3.64% of the mass of recycled powder, the water-cement ratio is 0.467-0.653, and the foam accounts for 9.7% of the total mass of cement and recycled powder.
[0008] The alkali-activated regenerated foam concrete is made of the following raw materials in parts by weight: 200 parts of total glue, 120 parts of cement, 0-80 parts of regenerated sand powder, 0-0.4 parts of sodium carbonate, 0-5.09 parts of sodium sulfate, 0-2.91 parts of sodium silicate, 93.4-130.6 parts of water and 19.4 parts of foam.
[0009] The alkali-activated regenerated foam concrete comprises the following raw materials in parts by weight: 200 parts of total glue, 120 parts of cement, 0-80 parts of regenerated micro powder, 0-0.4 parts of sodium carbonate, 0-5.09 parts of sodium sulfate, 0-2.91 parts of sodium silicate, 93.4-130.6 parts of water and 19.4 parts of foam.
[0010] The above cement is 42.5 grade rapid hardening sulphoaluminate cement.
[0011] The above-mentioned recycled sand and powder waste concrete is crushed and screened by a jaw crusher to remove coarse aggregate, and the remaining particle size is a mixture of sand and powder of 0-9.5mm, which is directly used after leaving the factory without any treatment. Among them, the particle sizes of 0-0.075mm, 0.075-0.15mm, 0.15-0.3mm, 0.3-0.6mm, 0.6-1.18mm, 1.18-2.36mm, 2.36-4.75mm and 4.75-9.5mm account for 3.1%, 3.5%, 6.8%, 10.7%, 8.1%, 15.5%, 25.6% and 26.7% respectively.
[0012] The above-mentioned recycled micropowder is waste concrete micropowder with a particle size of 0-0.075mm obtained by a dust collector when a construction waste plant treats waste concrete. The CaO, SiO2, Al2O3, Fe2O3, K2O, MgO, TiO2, MnO, SO3 and other chemical components in the recycled micropowder account for 28.41%, 31.73%, 4.63%, 6.81%, 6.21%, 8.59%, 3.42%, 1.13%, 2.15% and 6.92% respectively.
[0013] The sodium sulfate and sodium silicate are solid particles, the sodium carbonate is solid powder, and the sodium sulfate, sodium silicate and sodium carbonate are all analytically pure.
[0014] A method for preparing alkali-activated regenerated foam concrete, the method specifically comprising the following steps:
[0015] The first step is to prepare cement slurry according to a water-binder ratio of 0.467-0.653, and dilute the foaming agent 30 times to prepare a foam dilution;
[0016] The second step is to determine the foam dosage, determine the minimum and maximum foam dosage; set three foam production dosages between the minimum and maximum foam dosages to prepare five foam concretes with different dosages, test the dry density and thermal conductivity of the foam concrete to determine the foam dosage;
[0017] The third step is to determine the amount of recycled powder, and according to the determined foam amount, prepare foam concrete according to different percentages of recycled powder, and test the dry density and compressive strength of the foam concrete to determine the amount of recycled micro powder and recycled sand powder;
[0018] The fourth step is to determine the amount of activator. According to the determined foam content and recycled powder content, the activator content is designed, foam concrete is prepared, and the dry density and compressive strength of foam concrete are measured; the recycled powder content is greater than 40% and the dry density is less than 500kg / m 3 The compressive strength is greater than 0.5MPa and the amount of activator is determined;
[0019] The fifth step is to weigh the activator according to the determined activator dosage, and place the activator in a beaker and add water to dissolve it. The activator is added to the beaker. The activators in the beaker are sodium hydroxide, sodium carbonate, sodium silicate and sodium sulfate from bottom to top. After the activator is dissolved, pour the dissolved activator into the vertical pure slurry stirring pot;
[0020] Step 6: weigh the recycled powder according to the determined amount of recycled powder, weigh the sulphoaluminate cement and add them into the vertical pure slurry mixing pot, and stir for two minutes;
[0021] Step 7: prepare foam in the prepared foam dilution using a foaming machine, weigh the foam according to the determined foam dosage, and freeze the foam at 0 degrees Celsius for 60 seconds;
[0022] Step 8: Use a scraper to manually stir the cement slurry at the bottom of the vertical slurry stirring pot, add the weighed foam into the cement slurry, and then perform manual stirring and mechanical stirring to complete the preparation of the cement slurry;
[0023] The ninth step is to cast the prepared cement slurry into shape and demold it after 1-2 days, and then naturally cure it for 28 days.
[0024] The specific steps for determining the foam dosage in the above second step are: the mass of foam when the volume ratio of foam to cement slurry is 1:1 is taken as the minimum foam dosage, and the critical phase inversion is taken as the maximum foam dosage, that is, gradually adding foam to a relatively thin cement slurry, initially the continuous phase is cement slurry, and the dispersed phase is foam. When the foam is added to a certain dosage, the system undergoes a phase inversion, and becomes foam wrapping cement slurry. Stop adding foam, and gradually add drier cement slurry to the system. When the phase inversion occurs again, that is, the cement slurry wraps the foam, the percentage of foam relative to the total mass of cement and recycled powder at this time is the maximum foam dosage; set 3 more foam dosages between the minimum and maximum foam dosages, prepare foam concrete under 5 foam dosages, test the dry density and thermal conductivity, and determine the foam dosage;
[0025] The specific steps for stirring the cement slurry in the vertical slurry mixing pot in the above-mentioned eighth step are: tilt the vertical slurry mixing pot 45 degrees, stir manually for 5 seconds, then put the vertical slurry mixing pot back on the fixed frame, and stir mechanically for 15 seconds; remove the vertical slurry mixing pot, tilt the vertical slurry mixing pot 45 degrees, and stir manually for 30 seconds; put the vertical slurry mixing pot back on the fixed frame, and stir mechanically for 30 seconds.
[0026] Based on the above technical solution, the alkali-activated regenerated foam concrete and preparation method of the present invention have achieved the following technical advantages through practical application:
[0027] 1. The present invention provides a method for preparing alkali-activated regenerated foam concrete by using a vertical slurry stirring pot to stir and prepare cement slurry, and simultaneously uses a stirring method combining manual stirring and mechanical stirring, and manual stirring at 45 degrees to anti-gravity stirring and mixing, thereby improving the effect and quality of concrete mixing.
[0028] 2. The method for preparing alkali-activated regenerated foam concrete of the present invention improves the quality of foam mixing by freezing the foam during latex foam mixing and adding the foam according to the mass ratio instead of the volume ratio.
[0029] 3. The present invention discloses a method for preparing alkali-activated regenerated foamed concrete. The method adopts regenerated micro powder with silicon aluminum content as low as 37%, regenerated sand powder with particle size as high as 9.5 mm, and a small amount of activator. The method does not require grinding, and prepares 400-500 grade low-density foamed concrete with solid waste content as high as 40% and strength of 0.5-0.7 MPa. The density of foamed concrete in different pots is controlled at 480-510 kg / m 3 The density fluctuation of different test pieces in the same pot is controlled within ±10kg / m 3 Use vertical mixer to prepare 400-500kg / m 3 The foamed concrete is easy to clean; directly use low-quality recycled sand powder, with a dosage of up to 40%. Recycled sand powder 0-9.5mm, 4.75-9.5mm accounts for 25%, and the density of the foamed concrete is 490kg / m 3 About 0.5MPa in strength. For the first time, large-particle size and large-volume recycled sand powder were successfully used to prepare foamed concrete below grade 500; recycled micropowder with low silicon and aluminum content was efficiently used, with the dosage as high as 40%. The active silicon and aluminum content of the recycled micropowder was as low as 36%, and the foamed concrete made from it had the same solid waste disposal capacity and comparable performance as the foamed concrete made from recycled micropowder with an active silicon and aluminum content of 56%. Its density is 420kg / m 3 About, strength 0.7MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention discloses a foam slurry mixing diagram in which foaming is started at the nth second in the continuous foaming of alkali-activated regenerated foam concrete.
[0031] Figure 2 The invention discloses a foam slurry mixing diagram of frozen foam and room temperature foam in a method for preparing alkali-activated regenerated foam concrete.
[0032] Figure 3 This is a foam volume measurement diagram in a method for preparing alkali-activated regenerated foam concrete according to the present invention.
[0033] Figure 4The present invention is a schematic diagram of foam adhering to the inner wall of a pot in a method for preparing alkali-activated regenerated foam concrete.
[0034] Figure 5 The invention discloses a vertical stirring pot mixing foam diagram in a method for preparing alkali-activated regenerated foam concrete.
[0035] Figure 6 The present invention is a method for preparing alkali-activated regenerated foamed concrete and a schematic diagram of a mixture and a test block prepared by mixing and foaming in a horizontal mixer.
[0036] Figure 7 The present invention is a schematic cross-sectional view of foamed concrete in which an activator and a water reducer coexist in a method for preparing alkali-activated regenerated foamed concrete.
[0037] Figure 8 It is a schematic diagram of foam breaking when an activator and a water reducer coexist in a method for preparing alkali-activated regenerated foam concrete of the present invention.
[0038] Fig. 9 This is a schematic diagram comparing Example 3-3 and Comparative Example 18. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described below by the specific examples shown in the accompanying drawings. However, it should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0040] In the present invention, unless otherwise specified, "cement slurry" refers to a mixture of all raw materials except foam, which may be a mixture of cement, recycled micropowder, water, and activator, or a mixture of cement, recycled sand powder, water, and activator, or a mixture of cement and water. "Recycled powder" refers to recycled micropowder or recycled sand powder. "Mixed foam" refers to the mixture of foam and cement slurry. Total glue = cement + recycled micropowder, or total glue = cement + recycled sand powder. "S Si CH 1 / 1 / 1 / 1 1%" means that the mass ratio of sodium sulfate, sodium silicate, sodium carbonate, and sodium hydroxide is 1 / 1 / 1 / 1, and the total admixture is 1% of the mass of recycled powder. "Parts by weight" refers to the relative mass ratio relationship between the components, not the actual mass unit. According to the actual situation, 1 part by weight can be any mass such as 1kg, 10kg, etc. 42.5 Rapid hardening sulphoaluminate cement was purchased from Tangshan Polar Bear Cement Factory. Recycled sand powder was purchased from Shanghai Youhong Environmental Protection Technology Co., Ltd., with a particle size of 0-9.5mm. Recycled micro powder was purchased from Shanghai Puying Concrete Co., Ltd., with a particle size of 0-0.075 mm. Water was tap water. Foaming agent was purchased from Beijing Yashe Building Materials Co., Ltd., which was an animal protein foaming agent. The activator sodium silicate was purchased from Shanghai Shisihewei Chemical Co., Ltd., with a molecular formula of Na2SiO3·9H2O, analytically pure, colorless orthorhombic bipyramidal crystals, Na2O content of 19.3w / %-22.8w / %, Na2O to SiO2 ratio of 1.00-1.06, chloride (Cl) ≤0.01w / %, aluminum (Al) ≤0.05w / %, iron (Fe) ≤0.05w / %, heavy metals (in terms of Pb) ≤0.001w / %. Sodium sulfate was purchased from Sinopharm Chemical Reagent Co., Ltd., with the molecular formula of Na2SO4, analytically pure, colorless and transparent crystals, with a content of ≥99.0%, chloride (Cl) ≤0.001w / %, iron (Fe) ≤0.002w / %, and heavy metals (in terms of Pb) ≤0.005w / %. Sodium carbonate was purchased from Tianjin Zhiyuan Chemical Reagent Co., Ltd., with the molecular formula of Na2CO3, analytically pure, white powder, with a content (Na2CO3) ≥99.8%, chloride (Cl) ≤0.002w / %, iron (Fe) ≤0.0005w / %, and heavy metals (in terms of Pb) ≤0.0005w / %. Sodium hydroxide was purchased from Tianjin Hengxing Chemical Reagent Manufacturing Co., Ltd., with the molecular formula of NaOH, high purity, white crystalline particles, content (NaOH) ≥ 98.0%, chloride (Cl) ≤ 0.02w / %, aluminum (Al) ≤ 0.001w / %, iron (Fe) ≤ 0.005w / %, heavy metal (in terms of Pb) ≤ 0.001w / %. The dry density and compressive strength of foamed concrete were tested according to JG / T266-2011 "Foamed Concrete"; the thermal conductivity of foamed concrete was tested according to GB / T10294 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Protected Hot Plate Method".
[0041] Example 1
[0042] like Figure 1-8 The present invention belongs to an alkali-activated regenerated foam concrete, characterized in that the alkali-activated regenerated foam concrete comprises cement, regenerated powder, an activator, water and foam, the regenerated powder is one of regenerated micro powder and regenerated sand powder, the activator is at least one of sodium carbonate, sodium sulfate and sodium silicate, the cement accounts for 60% of the total mass of cement and regenerated powder, the regenerated powder accounts for 40% of the total mass of cement and regenerated powder, the sodium carbonate accounts for 0-0.5% of the mass of the regenerated powder, the sodium sulfate accounts for 0-6.36% of the mass of the regenerated powder, the sodium silicate accounts for 0-3.64% of the mass of the regenerated powder, the water-cement ratio is 0.467-0.653, and the foam accounts for 9.7% of the total mass of cement and regenerated powder.
[0043] P1, determine the water consumption; take 700g of cement and place it in a vertical slurry mixing pot, gradually add water to 340g, the cement slurry is bright and smooth, stop adding water, at this time the water-cement ratio is 340 / 700=0.486;
[0044] P2, prepare foam at a dilution factor of 30; put 200g of foaming agent and 6000g of water in a plastic bucket and shake evenly to prepare foam;
[0045] P3, determine the minimum foam dosage; put the cement slurry into a plastic measuring cup and use a marker to draw a line on the outer wall of the measuring cup at the cement slurry surface. Pour the cement slurry back into the mixing pot and clean the measuring cup. Put the measuring cup on a scale, peel it, add water to the measuring cup to the drawn line, weigh the water mass to be 615g, then the volume of water is 615mL, then the volume of cement slurry is 615mL, and the density of cement slurry is (700+340) / 615=1691kg / m 3 =1691g / L; Pour out the water, put the measuring cup on the scale, peel it, add foam to the measuring cup to the drawn line, weigh the mass of the foam to be 28g, get a volume of 615mL of foam, and measure the density of the foam to be 28g / 615mL*1000=45.5kg / m 3 =45.5g / L. When the foam and cement slurry have the same volume, the ratio of foam content to cement content is 28 / 700=4%, that is, the minimum foam content is 4%;
[0046] P4, determine the maximum foam dosage by critical phase inversion; take 700g of cement and 340g of water (water-cement ratio of 0.486, cement slurry with thin glue) and place them in a vertical pure slurry stirring pot and stir them evenly. Place a small basin on the scale, peel it, weigh 100g of foam, and gradually add foam to the stirring pot. Initially, the cement slurry wraps the foam. Add the foam until a certain moment, and the foam wraps the cement slurry. Stop adding foam. Weigh the remaining foam in the small basin to be 28g, and then add 72g of foam. Place a small basin on the scale, peel it, weigh 100g of cement and 30g of water (water-cement ratio of 0.3, cement slurry with dry glue), stir them evenly with a scraper, and gradually add cement slurry to the stirring pot. Initially, the foam wraps the cement slurry. Add cement slurry until a certain moment, and the cement slurry wraps the foam. Stop adding cement slurry. Weigh the remaining cement slurry in the small basin to be 114g, and then add 130-114=26g of cement slurry, including 20g of cement and 6g of water. Then total cement = 700 + 20 = 720g, total water = 340 + 6 = 346g, water-cement ratio = 346 / 720 = 0.481, then the ratio of foam content to cement content when the critical phase is reversed is 72 / 720 = 10%, that is, the maximum foam content is 10%;
[0047] P5, set three foam dosages of 7%, 8.5%, and 9.7% between the lowest foam dosage of 4% and the highest foam dosage of 10%, and prepare foam concrete with 5 foam dosages. The dry densities of foam concrete with foam dosages of 4%, 7%, 8.5%, 9.7%, and 10% are 1019, 779, 600, 484, and 464 kg / m respectively. 3 The thermal conductivity coefficients are 0.175, 0.158, 0.124, 0.087, and 0.078 W / (m·K) respectively. Based on this, the relationship between foam content and density is as follows: when foam content is >9.7%, density is <500 kg / m 3 The relationship between density and thermal conductivity is: density <500kg / m 3 Thermal conductivity <0.1W / (m·K). Based on the relationship between foam content, density and thermal conductivity and the requirement that the thermal conductivity is less than 0.1W / (m·K), the foam content is determined to be 9.7%.
[0048] P6, fixed foam content of 9.7%, designed recycled micro powder content of 0, 20%, 40%, 60%, 80%, recycled sand powder content of 0, 20%, 40%, 60%, 80%, prepared foam concrete, tested recycled micro powder content of 0, 20%, 40%, 60%, 80%, the dry density of foam concrete was 484, 453, 446, 424, 374 kg / m 3The compressive strength is 0.8, 0.6, 0.5, 0.3, 0.1MPa respectively; the dry density of foam concrete is 484, 580, 497, 447, 395kg / m when the recycled sand powder content is 0, 20%, 40%, 60%, 80% respectively. 3 The compressive strengths are 0.8, 1.2, 0.5, 0.3 and 0.1 MPa respectively. Based on the principle of high recycled powder content and high strength, the content of recycled micro powder and recycled sand powder is determined to be 40%.
[0049] P7, fixed foam content 9.5%, recycled powder content 40%, designed activator content, prepared foam concrete, and measured dry density and compressive strength. 3 , compressive strength greater than 0.5MPa is used as an indicator, and the activator dosage of recycled micro-powder-based foamed concrete is determined to be C 0.5%, S Si 7 / 4 10%, and the activator dosage of recycled sand powder-based foamed concrete is S Si 7 / 4 7%.
[0050] P8, according to the determined activator dosage, weigh the activator, and place the activator in a beaker and add water to dissolve it. Add the activator to the beaker. The activators in the beaker are sodium hydroxide, sodium carbonate, sodium silicate and sodium sulfate from bottom to top. After the activator is dissolved, pour the dissolved activator into the vertical pure slurry stirring pot;
[0051] P9, weigh the recycled powder according to the determined amount of recycled powder, weigh the sulphoaluminate cement and add them together into the vertical pure slurry mixing pot, and stir for two minutes;
[0052] P10, using a foaming machine to prepare foam in the prepared foam dilution, weighing the foam according to the determined foam dosage, and freezing the foam at 0 degrees Celsius for 60 seconds;
[0053] P11, use a scraper to manually stir the cement slurry at the bottom of the vertical slurry mixing pot evenly, and add the weighed foam to the cement slurry; tilt the vertical slurry mixing pot 45 degrees, stir manually for 5 seconds, then put the vertical slurry mixing pot back on the fixed frame, and stir mechanically for 15 seconds; remove the vertical slurry mixing pot, tilt the vertical slurry mixing pot 45 degrees, and stir manually for 30 seconds; put the vertical slurry mixing pot back on the fixed frame, and stir mechanically for 30 seconds; the cement slurry is prepared;
[0054] P12, cast the prepared cement slurry into shape and demold it after 1-2 days, and naturally cure it for up to 28 days.
[0055]
[0056] Table 1 Alkali activated recycled foam concrete mix design
[0057] Through the new foam concrete mix design, the dosage of each component is determined, and the foam concrete is prepared without calculating the ratio. The critical phase inversion is used to ensure the maximum foam dosage. The minimum foam dosage is determined with equal volumes of foam and cement slurry. Three foam dosages are set in the middle, and the appropriate foam dosage is determined based on the corresponding relationship between foam dosage-density-thermal conductivity and the requirements of thermal conductivity. The dosage of recycled micro powder, recycled sand powder, and activator is designed to determine the content of each component.
[0058] Comparative Example 1
[0059] The difference between this comparative example and Example 1 is that the step "P4 determines the maximum foam dosage by critical phase inversion" is changed to "determine the maximum foam dosage by dichotomy". The dichotomy method for determining the maximum foam dosage in this comparative example is shown in Table 2. The dichotomy method for determining the maximum foam dosage is as follows:
[0060] P4. Use the dichotomy method to gradually approach the maximum foam dosage. Design cement slurry 1L, foam 9L, calculate cement slurry mass = 1L*1691g / L=1691g, cement = 1691 / (700+340)*700=1138g, cement slurry water = 1691 / (700+340)*340=553g, foam = 9L*45.5g / L=409.5g, foaming agent = 409.5 / 30=13.65g, foaming agent water = 13.65*29=395.85g. Prepare foamed concrete, the result is that the foam wraps the cement slurry, and the mixing fails. Fix the cement slurry volume to 1 part, use the dichotomy method to take the middle value of 5 parts between the foam volume of 1 part and 9 parts, design the cement slurry volume of 1 part, the foam volume of 5 parts, the total volume of foam and cement slurry is 10L, calculate the mass of each component, prepare foamed concrete, the result is that the foam wraps the cement slurry, and the mixing fails. The volume of cement slurry was fixed at 1 part, and 3 parts of the middle value between 1 part and 5 parts of foam were taken by dichotomy. The designed volume of cement slurry was 1 part, the volume of foam was 3 parts, and the total volume of foam and cement slurry was 10L. The mass of each component was calculated to prepare foamed concrete. As a result, the foam wrapped the cement slurry and the mixing failed. The volume of cement slurry was fixed at 1 part, and 2 parts of the middle value between 1 part and 3 parts of foam were taken by dichotomy. The designed volume of cement slurry was 1 part, the volume of foam was 2 parts, and the total volume of foam and cement slurry was 10L. The mass of each component was calculated to prepare foamed concrete. As a result, the cement slurry wrapped the foam and the mixing was successful. The volume of cement slurry was fixed at 1 part, and 2.5 parts of the middle value between 2 parts and 3 parts of foam were taken by dichotomy. The designed volume of cement slurry was 1 part, the volume of foam was 2.5 parts, and the total volume of foam and cement slurry was 10L. The mass of each component was calculated to prepare foamed concrete. As a result, the cement slurry wrapped the foam and the mixing was successful. The volume of cement paste is fixed at 1 part, and the middle value of 2.75 parts is taken from the foam volume of 2.5 parts and 3 parts by dichotomy. The cement paste volume is designed to be 1 part, the foam volume is 2.75 parts, and the total volume of foam and cement paste is 10L. The mass of each component is calculated and foamed concrete is prepared. As a result, the foam wraps the cement paste and the mixing fails. The maximum foam dosage is 2.5 parts, and the proportion of foam mass to cement mass is 325 / 3251=10%.
[0061] Table 2
[0062] Determine the maximum foam dosage by dichotomy
[0063]
[0064] The maximum foam content was found to be 10%. Example 1 used the critical phase inversion method to prepare one pot of concrete, and Comparative Example 1 used the dichotomy method to prepare 6 pots of concrete, which wasted manpower and had low efficiency.
[0065] Comparative Example 2
[0066] The difference between this comparative example and Example 1 is that step P4 "gradually add foam to the thinner (water-cement ratio 0.486) cement slurry, and after phase inversion, gradually add the drier (water-cement ratio 0.3) cement slurry" is changed to "gradually add foam to the drier (water-cement ratio 0.3) cement slurry, and after phase inversion, gradually add the thinner (water-cement ratio 0.486) cement slurry". As a result, the foam breaks when in contact with the drier cement slurry, and the foam mixing fails.
[0067] Comparative Example 3
[0068] The difference between this comparative example and Example 1 is that step P4 "gradually add foam to the thinner (water-binder ratio 0.486) cement slurry, and after phase inversion, gradually add the drier (water-binder ratio 0.3) cement slurry" is changed to "gradually add foam to the thinner (water-binder ratio 0.486) cement slurry, and after phase inversion, gradually add the thinner (water-binder ratio 0.486) cement slurry". As a result, 20g of cement and 9.72g of water were added for the second time, the total water-binder ratio was 0.486, the foam content was 10%, and the mold was destroyed after demolding.
[0069] Combining Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the thinner cement slurry improves the "compatibility" of the foam slurry, ensuring the successful mixing of the foam slurry, and the drier cement slurry improves the strength of the foam concrete.
[0070] Example 2
[0071] This embodiment provides a method for preparing alkali-activated regenerated foam concrete. The mix ratio and performance of the alkali-activated regenerated foam concrete in this embodiment are shown in Table 1. The preparation method comprises the following steps:
[0072] S1, weigh a batch of foaming agent and foaming agent dilution water, and put them into a large barrel;
[0073] S2, called the stimulator, is wrapped in paper;
[0074] S3, weigh water and add it to the empty bottle;
[0075] S4, called recycled powder, added to a plastic bag; called sulphoaluminate cement, added to the same plastic bag;
[0076] S5, air compressor, large barrel, small barrel, and socket outlet are placed next to the vertical pure pulp mixer. Plug the power cord of the air compressor into the socket outlet. Tie a weight to the mouth of the thin tube (i.e. the liquid suction tube) with a rubber band to let the liquid suction tube automatically settle to the bottom of the foaming agent diluent. Put the thick tube (i.e. the foaming chamber) in the large barrel. Put the small barrel next to the large barrel;
[0077] S6, add activators to the beaker, put the easily soluble ones at the bottom and the insoluble ones at the top, from bottom to top, they are sodium hydroxide, sodium carbonate, sodium silicate and sodium sulfate;
[0078] S7, add water to the beaker while stirring with a glass rod to dissolve the activator in all the water, and pour into the vertical pure slurry stirring pot;
[0079] S8, adding cement and recycled powder into the vertical slurry mixing pot and stirring for 2 minutes;
[0080] S9, foaming; first turn the main switch of the foaming machine clockwise, and after the display counts down for 3 seconds, press the air compression switch to start foaming. Add the liquid from the front into the big bucket, and once foam appears, start to take the foam after 3 seconds. Immediately move the tube to the small bucket, take a certain amount of foam, first press the air compression switch and then press the main switch of the foaming machine to turn off the air compressor;
[0081] S10, placing the foam in a refrigerator at 0 degrees Celsius for 60 seconds;
[0082] S11, place a small basin on the scale, peel it, and weigh a certain mass of foam;
[0083] S12, taking down the vertical slurry mixing pot, manually stirring the cement slurry at the bottom of the pot with a scraper, and adding the weighed foam into the cement slurry;
[0084] S13, manual stirring. Tilt the vertical pure slurry stirring pot 45 degrees and stir manually for about 5 seconds;
[0085] S14, mechanical stirring. Put the vertical pure slurry stirring pot back on the fixed frame and mechanically stir for about 15 seconds;
[0086] S15, manual stirring. Remove the vertical pure slurry stirring pot, tilt the vertical pure slurry stirring pot 45 degrees, and stir manually for about 30 seconds;
[0087] S16, mechanical stirring: put the vertical pure slurry stirring pot back on the fixed frame, and mechanically stir for about 30 seconds;
[0088] S17, pouring and molding, demoulding after 1-2 days, and natural curing up to 28 days.
[0089] Comparative Example 4
[0090] The difference between this comparative example and Example 2 is that the step S9 in which "once foam appears, the timing is 3 seconds and the foam is taken" is changed to "once foam appears, the timing is n seconds and the foam is taken, where n is random and different each time". The mix ratio of the alkali-activated regenerated foam concrete in this comparative example is the S Si 7 / 4 4% formula in Table 1. The mixing diagram of the alkali-activated regenerated foam concrete is shown in Table 1. Figure 1 shown.
[0091] Depend on Figure 1It can be seen that the foam is collected from the nth second after the continuous foam appears. If the time of collecting the foam from the foam outlet of the foaming machine is inconsistent each time, the density of the foam emitted each time will be inconsistent. Each time the foam is added is measured by mass, the volume of foam added to the slurry will be inconsistent, which will lead to inconsistent density of the foamed concrete.
[0092] Comparative Example 5
[0093] The difference between this comparative example and Example 2 is that step "S10, placing the foam in a refrigerator and freezing it at 0 degrees Celsius for 60 seconds" is deleted. The proportion of the alkali-activated regenerated foam concrete in this comparative example is the formula of S Si 7 / 4 7%, SC 7 / 1 7%, C1% in Table 1. The foam slurry mixing diagram of the frozen foam and the room temperature foam is shown in Figure 2 shown.
[0094] Depend on Figure 2 It can be seen that the foams in the first three samples after freezing are more solid and less likely to leak water when placed, and the foam concrete produced has greater strength. The foams in the last three samples at room temperature are more liquid and more likely to leak water when placed, and the foam concrete produced has lower strength.
[0095] Comparative Example 6
[0096] The difference between this comparative example and Example 2 is that the step "S1, weigh a batch of foaming agent, foaming agent dilution water, and put them into a large barrel." is changed to "weigh a pot of foaming agent, foaming agent dilution water, and put them into a small barrel." and the step "S11, place a small basin on the scale, peel it, and weigh a certain mass of foam." is deleted. In other words, Example 2 is to prepare a large barrel of foaming agent dilution liquid, and when mixing each pot of foamed concrete, foam is generated once and the foam mass is weighed and mixed, and the remaining foaming agent dilution liquid is retained for standby use, and the foam content is measured by the foam mass. Comparative Example 3 is to prepare a foaming agent dilution liquid once when mixing each pot of foamed concrete, and then foam and mix the foam. Each time the foaming agent dilution liquid is completely used up, and the foam content is measured by the foaming agent mass. The proportions of the alkali-activated regenerated foam concrete described in this comparative example are shown in Table 3.
[0097] Comparative Example 7
[0098] The difference between this comparative example and Example 2 is that the step "S11, place a small basin on the scale, peel it, and weigh a certain mass of foam." is changed to "Use a plastic measuring cup to weigh a certain volume of foam." The proportions of the alkali-activated regenerated foam concrete described in this comparative example are shown in Table 3. Example 2, Comparative Example 6, and Comparative Example 7 have the same proportions, and the foam is measured in different ways. The mass of foam is 9.7% of the total mass of glue, that is, 19.4g. Example 2 weighs 19.4g of foam. Comparative Example 6 weighs 19.4g of foam diluent based on the fact that the mass of the foaming agent diluent before foaming is equal to the mass of foam after foaming. Because (foaming agent + water) / foaming agent = 30, 0.65g of foaming agent and 18.75g of water are weighed. Comparative Example 7 obtains the foam volume based on the ratio of foam mass to foam density. Because the foam density is 45.5g / L measured in step P3 of Example 1, the foam volume is
[0099] =19.4g / 45.5g / L=426mL.
[0100] Table 3
[0101] Foam concrete prepared by different ways of metering foam
[0102]
[0103] As can be seen from Table 3, in Example 2, the foam is measured by mass, and the dry density of foamed concrete in different pots is slightly different, that is, how many grams of foam are added to 100g of cement, and foamed concrete of a specified density can be obtained by adding foam in this way. In Comparative Example 6, the foam is measured by the mass of the foaming agent, and the dry density varies greatly. This is because the suction tube of the foaming machine needs to be sunk to the bottom of the foaming agent dilution to maintain a liquid-sealed state in order to avoid vacuuming. Each time the air compressor is turned off, some foaming agent dilution still remains in the small bucket, and the mass of the foaming agent added to the system each time is inconsistent. In Comparative Example 4, the foam is measured by the foam volume, and the dry density fluctuates greatly. This is because the foam is similar to an irregular solid and cannot fill the gaps in the measuring cup, resulting in inaccurate volume measurement, see Figure 3 shown.
[0104] Comparative Example 8
[0105] The difference between this comparative example and Example 2 is that step "S13 manual stirring 5s" is deleted, step "S14 mechanical stirring 15s" is changed to "mechanical stirring 20s", and the total stirring time remains unchanged. That is, the stirring of "mobile phone" in Example 2 is changed to "machine phone". The proportion of alkali-activated regenerated foam concrete in this comparative example is the S Si 7 / 4 4% formula in Table 1. As a result, the foam sticks to the inner wall of the pot and the stirring blade, and it is a waste of time to scrape it off. Figure 4 shown.
[0106] Comparative Example 9
[0107] The difference between this comparative example and Example 2 is that step "S14 mechanical stirring 15s", step "S15 manual stirring 30s", and step "S16 mechanical stirring 30s" are deleted, and step "S13 manual stirring 5s" is changed to "manual stirring 80s", and the total stirring time remains unchanged. That is, the stirring of "mobile phone" in Example 2 is changed to "hand" stirring. The proportion of the alkali-activated regenerated foam concrete described in this comparative example is the S Si 7 / 4 4% formula in Table 1. As a result, the manual stirring time is too long and laborious. When doing a multi-pot test, the stirring speed decreases and the efficiency becomes low.
[0108] Comparative Example 10
[0109] The difference between this comparative example and Example 2 is that step "S13 manual stirring for 5s", step "S14 mechanical stirring for 5s", and step "S15 manual stirring for 30s" are deleted, and step "S16 mechanical stirring for 30s" is changed to "mechanical stirring for 80s", and the total stirring time remains unchanged. That is, the stirring of "mobile phone" in Example 2 is changed to "machine" stirring. The proportion of alkali-activated regenerated foam concrete in this comparative example is the S Si 7 / 4 4% formula in Table 1. As a result, there is no manual stirring at a 45-degree tilt, and the vertical mixer is always used for stirring. The cement slurry should have wrapped the foam, but the foam wrapped the cement slurry. After molding, the bubbles become significantly larger and the mold collapses.
[0110] Comparative Example 11
[0111] The difference between this comparative example and Example 2 is that the step "mechanical stirring for 30s in S16" is deleted, and the step "mechanical stirring for 15s in S14" is changed to "mechanical stirring for 45s", and the total stirring time remains unchanged. That is, the stirring of "mobile phone" in Example 2 is changed to "mobile phone hand" stirring. The proportion of the alkali-activated regenerated foam concrete in this comparative example is the S Si 7 / 4 4% formula in Table 1, the total glue is changed from 200g to 600g, and the "vertical slurry stirring pot (or machine)" is changed to "vertical mortar stirring pot (or machine)". The dry density test value of the alkali-activated regenerated foam concrete is shown in Table 4.
[0112] Table 4
[0113] Dry density test values of different test blocks of the same pot of foam concrete
[0114]
[0115] Example 2 adopts the method of manual stirring-mechanical stirring-manual stirring-mechanical stirring to mix foam. The dry density of different test blocks of the same pot of foam concrete is (460±10) kg / m 3 Comparative Example 11 adopts manual stirring-mechanical stirring-manual stirring to mix foam, and the dry density of different test blocks in the same pot of foam concrete is (470±120) kg / m3 , with large fluctuations.
[0116] In summary, from Comparative Examples 8 to Comparative Examples 11, it can be seen that in the preparation process, the foam is first mixed manually to stir the foam into the cement slurry to avoid sticking to the stirring blade; then the foam is mixed mechanically to save labor; then the foam is mixed manually to achieve the purpose of uniformity between the upper and lower parts; and then the foam is mixed mechanically to make the density of the slurry in the six molds consistent.
[0117] Comparative Example 12
[0118] The difference between this comparative example and Example 2 is that the "vertical slurry mixer" in step S5 is changed to "horizontal concrete mixer", the "vertical slurry mixing pot" in steps S7-S8 is changed to "horizontal concrete mixer", and the manual-motorized-manual-motorized stirring in steps S12-S16 is changed to "add the weighed foam to the horizontal concrete mixer, mix and stir with the cement slurry for 80s to make it uniform." The proportion of the alkali-activated regenerated foam concrete in this comparative example is the S Si7 / 4 4% formula in Table 1. The mixture and test block prepared by the horizontal mixer are shown in Table 1. Figure 6 shown.
[0119] Depend on Figure 6 It can be seen that the capacity of the horizontal concrete mixer is 60L, which is not suitable for adjusting the proportion of small samples. The mixing shaft is not wetted, the test blocks are not fully filled, and the surface is not smooth and uniform. Moreover, the cleaning of the horizontal mixer requires the pot mouth to be rotated to 45 degrees downward, and the dirty water is poured out, which pollutes the ground and is difficult to clean. The slurry is easy to stick to the wall to form mud, which is not easy to scrape, and at least 2 people are required for the test. In addition, once the bedroom mixer has mixed fiber concrete, the pot wall, mixing shaft, and mixing blades are always sticky with mud when doing other tests later, and even a hammer cannot knock it off. The capacity of the vertical pure pulp mixer and the vertical mortar mixer is only 2.2 and 4.5L, which are suitable for mixing small samples. The mixing pot is detachable and can be directly placed in the sink for cleaning without polluting the ground. Only one person is needed for the test, which reduces labor. Even if the fiber slurry is mixed, the cleaning area is small, which greatly reduces the difficulty of cleaning. However, the vertical mixer mixes the foam unevenly, and the upper slurry is 200kg / m lighter than the lower slurry. 3 , as shown in Table 4. This patent adopts manual-motorized-manual-motorized stirring to solve the problem of uneven foam mixing in vertical mixers.
[0120] Example 3
[0121] This embodiment provides a group of alkali-activated regenerative foamed concrete. The preparation method of the alkali-activated regenerative foamed concrete is shown in Example 2. The proportion and performance of the alkali-activated regenerative foamed concrete are shown in Table 5. Example 3-1, Example 3-2, and Example 3-3 are respectively the formulas of C 0.5%, S Si 7 / 4 10%, and S Si 7 / 4 7% in Table 1.
[0122] Table 5
[0123] Example 3 Proportion and performance of alkali-activated regenerated foam concrete
[0124] Example 3-1 Example 3-2 Example 3-3 Total rubber / g 200 200 200 Cement / g 120 120 120 Recycled micro powder / g 80 80 0 Regenerated sand powder / g 0 0 80 Sodium carbonate / g 04 0 0 Sodium sulfate / g 0 5.09 3.56 Sodium silicate / g 0 2.91 2.04 Water / g 109.6 130.6 93.4 Foam dosage / g 19.4 19.4 19.4 cement 60% 60% 60% Recycled Micro Powder 40% 40% 0 Recycled sand powder 0 0 40% Sodium carbonate 0.5% 0 0 Sodium sulfate 0 6.36% 4.45% Sodium silicate 0 3.64% 2.55% Water-cement ratio 0.548 0.653 0.467 Foam dosage 9.7% 9.7% 9.7% Dry density / (kg / m3) 421 454 489 Compressive strength / MPa 0.7 0.7 0.5 Thermal conductivity / (W / (m·K)) 0.071 0.079 0.087
[0125] As shown in Table 5, the dry density of the alkali-activated regenerated foam concrete prepared in this patent is 421-489 kg / m 3 , compressive strength 0.5-0.7MPa, thermal conductivity 0.071-0.087W / (m·K), recycled powder content 40%. Recycled micro-powder-based foamed concrete is lighter and stronger than recycled sand powder-based foamed concrete. This is because the particle size of the recycled micro-powder is less than 0.075mm, which can form a continuous phase with cement and has a fine filling effect. However, there are fewer intermediate particles in the recycled sand powder, more ultra-fine and ultra-coarse particles, and the grading is poor. Example 3-3 uses large-particle recycled sand powder to prepare ultra-small pore foamed concrete, see Fig. 9 Formula: S Si 7 / 47%, water-binder ratio 0.467.
[0126] Comparative Example 13
[0127] This comparative example provides a group of foamed concrete. The foamed concrete ratio is the other test formulas except the three formulas of C0.5%, S Si 7 / 410%, and S Si 7 / 47% in Table 1, and the preparation method is shown in Example 2. The foamed concrete prepared by the formula of 40% recycled micropowder without activator in Table 1 is used as a blank control, and its density is 446kg / m 3 Strength 0.5MPa, Example 3-1C 0.5% formula foam concrete density 421kg / m 3 Strength 0.7MPa, lighter and stronger than the blank control; Example 3-2S Si 7 / 4 10% formula foam concrete density 454kg / m 3 The strength is 0.7MPa, which is equivalent to the blank control in density and greater in strength. The foamed concrete made with the formula of 40% recycled sand powder without activator in Table 1 is used as the blank control, and its density is 497kg / m 3 Strength 0.5MPa, density of foamed concrete prepared by Example 3-3S Si 7 / 4 7% formula 489kg / m 3 The strength is 0.5MPa, which is equivalent to the blank control in strength and lighter in density. Table 1 The density of foamed concrete made with 20% recycled micropowder in the recycled micropowder test is 453kg / m 3 The strength is 0.6MPa, while the density of the foamed concrete made by Example 3-2 using 40% recycled micro powder and 7 / 410% S Si is 454kg / m 3The strength is 0.7MPa, and the performance is the same, and the amount of recycled micro powder consumption is increased by 1 times. In the activator test in Table 1, except for the three formulas of C0.5%, S Si 7 / 4 10%, and S Si 7 / 4 7%, the other activator formulas do not have the advantages of light weight and high strength compared with the blank control without activator. This shows that most activator formulas have no reinforcing effect on recycled foam concrete with a density below 500, and only a few activator formulas such as C 0.5%, S Si 7 / 4 10%, and S Si 7 / 4 7% have an reinforcing effect. This is the first conclusion drawn in the literature.
[0128] Comparative Example 14
[0129] This comparative example is used to illustrate that the activator and water reducer cannot coexist. Because the activator has little effect on the strengthening of recycled foam concrete, it is assumed that the water-binder ratio can be reduced by adding a water reducer to improve the strength of recycled foam concrete. The proportion, performance and cross-section of the foam concrete described in this comparative example are shown in Figure 7 shown.
[0130] Depend on Figure 7 It can be seen that the pore size of foamed concrete is small when there is no water reducer / no activator, only water reducer, and only activator. When water reducer / activator coexists, the pore size increases, causing the foamed concrete to lose strength. This is because the activators sodium sulfate, sodium silicate, and sodium carbonate are salts. The addition of water reducers increases the concentration of salts. High concentrations of salts will rob the bound water in the protein, causing the animal protein foaming agent to be destroyed, thus causing the foam to burst and the foamed concrete to collapse. Figure 8 As shown. No foam breaking occurs when there is no water reducing agent.
[0131] Comparative Example 15
[0132] The difference between this comparative example and Example 3-1 is that the chemical composition of the regenerated micropowder is different and no activator is added, as shown in Tables 6 and 7.
[0133] Table 6
[0134] Chemical composition of recycled micro powder
[0135]
[0136] Table 7
[0137] Comparison between Example 3-1 and Comparative Example 15
[0138]
[0139]
[0140] It can be seen from Table 7 that the active silicon aluminum content in the regenerated micropowder of Comparative Example 15 is about 56%, and the active silicon aluminum content in the regenerated micropowder of Example 3-1 is about 36%. When the performance and solid waste disposal amount are equivalent, this patent uses lower quality regenerated micropowder.
[0141] Comparative Example 16
[0142] The difference between this comparative example and Example 3-3 is that the particle size of the regenerated sand powder is different, as shown in Table 8.
[0143] Table 8
[0144] Comparison of Example 3-3 and Comparative Example 16
[0145]
[0146] As shown in Table 8, the particle size of the recycled sand powder in Comparative Example 16 is smaller, and the crushing and screening consume more energy. In Example 3-3, the recycled sand powder of 4.75-9.5 mm accounts for 27%. Under the condition of equivalent performance and solid waste disposal, this patent uses recycled sand powder of lower quality. Recycled sand powder of 0-9.5 mm, 4.75-9.5 mm accounts for 27%, can be used to prepare foamed concrete, which is the first successful case in the literature of using such large particle size and large amount of recycled sand powder to prepare foamed concrete below grade 500.
[0147] Comparative Example 17
[0148] The difference between this comparative example and Example 3-1 is that the water-to-binder ratio is 0.2, as shown in Table 8.
[0149] Table 9
[0150] Comparison between Example 3-1 and Comparative Example 17
[0151]
[0152]
[0153] From Table 9, we can see that the dry density is 420kg / m 3 The strength of foamed concrete with a water-binder ratio of 0.2 is 0.3MPa, and the strength of foamed concrete with a water-binder ratio of 0.548 is 0.7MPa. For low-density foamed concrete below grade 500, the strength increases instead of decreases by increasing the water-binder ratio.
[0154] Comparative Example 18
[0155] The difference between this comparative example and Example 3-3 is that the water-binder ratio is 0.2. Fig. 9 shown.
[0156] Depend on Fig. 9It can be seen that the particle size of the regenerated sand powder is 0-9.5mm. When the water-binder ratio is low, the foam is punctured by the sharp regenerated sand powder and turns into water. The mixture is not mixed with foam, but becomes thinner, and the mixing of foam fails. When the water-binder ratio is high, the texture of the mixture is uniform and the pore size is fine after hardening.
[0157] In summary, the innovation of the present invention lies in weighing the foam quality, 45 degrees manual + vertical + 45 degrees manual + vertical, incompatibility of water reducer and activator, enhancement of water-cement ratio, critical phase inversion, and freezing of foam, which realizes the technical effects of easy cleaning and foam mixing of the mixer, high-precision density control, small and stable foam, fine pore size of foam concrete, high disposal capacity of low-quality construction waste, small amount of activator, and 400-500 grade foam concrete strength of 0.5-0.7MPa.
[0158] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. An alkali-activated regenerated foam concrete, characterized in that: The alkali-activated regenerated foam concrete is made of cement, regenerated powder, activator, water and foam, wherein the regenerated powder is one of regenerated micro powder and regenerated sand powder, the activator is at least one of sodium carbonate, sodium sulfate and sodium silicate, the cement accounts for 60% of the total mass of cement and regenerated powder, the sodium carbonate accounts for 0-0.5% of the mass of the regenerated powder, the sodium sulfate accounts for 0-6.36% of the mass of the regenerated powder, the sodium silicate accounts for 0-3.64% of the mass of the regenerated powder, the water-binder ratio is 0.467-0.653, and the foam accounts for 9.7% of the total mass of cement and regenerated powder; The regenerated sand powder is a mixture of sand and powder with a particle size of 0-9.5 mm remaining after the waste concrete is crushed and screened by a jaw crusher to remove the coarse aggregate, and is directly used after leaving the factory without treatment; The regenerated fine powder is waste concrete fine powder with a particle size of 0-0.075 mm obtained by using a dust collector when a construction waste plant treats waste concrete.
2. The alkali-activated regenerated foamed concrete according to claim 1, characterized in that: The alkali-activated regenerated foam concrete is made of the following raw materials in parts by weight: 120 parts of cement, 80 parts of regenerated sand powder, 0-0.4 parts of sodium carbonate, 0-5.09 parts of sodium sulfate, 0-2.91 parts of sodium silicate, 93.4-130.6 parts of water and 19.4 parts of foam.
3. The alkali-activated regenerated foamed concrete according to claim 1, characterized in that: The alkali-activated regenerated foam concrete is made of the following raw materials in parts by weight: 120 parts of cement, 80 parts of regenerated micropowder, 0-0.4 parts of sodium carbonate, 0-5.09 parts of sodium sulfate, 0-2.91 parts of sodium silicate, 93.4-130.6 parts of water and 19.4 parts of foam.
4. The alkali-activated regenerated foamed concrete according to any one of claims 1 to 3, characterized in that: The cement is 42.5 grade rapid hardening sulphoaluminate cement.
5. The alkali-activated regenerated foamed concrete according to any one of claims 1 to 2, characterized in that: In the regenerated sand powder, the particle sizes of 0-0.075mm, 0.075-0.15mm, 0.15-0.3mm, 0.3-0.6mm, 0.6-1.18mm, 1.18-2.36mm, 2.36-4.75mm and 4.75-9.5mm account for 3.1%, 3.5%, 6.8%, 10.7%, 8.1%, 15.5%, 25.6% and 26.7% respectively.
6. The alkali-activated regenerated foamed concrete according to any one of claims 1 to 3, characterized in that: The CaO, SiO2, Al2O3, Fe2O3, K2O, MgO, TiO2, MnO, SO3 and other chemical components in the regenerated micropowder account for 28.41%, 31.73%, 4.63%, 6.81%, 6.21%, 8.59%, 3.42%, 1.13%, 2.15% and 6.92% respectively.
7. The alkali-activated regenerated foamed concrete according to any one of claims 1 to 3, characterized in that: The sodium sulfate and sodium silicate are solid particles, the sodium carbonate is solid powder, and the sodium sulfate, sodium silicate and sodium carbonate are all analytically pure.
8. A method for preparing alkali-activated regenerated foam concrete, characterized in that: The method specifically comprises the following steps: The first step is to prepare cement slurry according to a water-binder ratio of 0.467-0.653, and dilute the foaming agent 30 times to prepare a foam dilution solution; The second step is to determine the foam dosage, determine the minimum and maximum foam dosage; set three foam dosages between the minimum and maximum foam dosages, prepare five foam concretes with different dosages, test the dry density and thermal conductivity of the foam concrete to determine the foam dosage; The specific steps for determining the foam dosage in the second step are: the mass of foam when the volume ratio of foam to cement slurry is 1:1 is taken as the minimum foam dosage, and the critical phase inversion is taken as the maximum foam dosage, that is, gradually adding foam to cement slurry with a water-binder ratio of 0.486, initially the continuous phase is cement slurry, and the dispersed phase is foam. When the foam is added to a certain dosage, the system undergoes a phase inversion, and the cement slurry is wrapped by foam. The addition of foam is stopped, and cement slurry with a water-binder ratio of 0.3 is gradually added to the system. When the phase inversion occurs again, that is, the cement slurry wraps the foam, the percentage of foam relative to the total mass of cement and recycled powder at this time is the maximum foam dosage; 3 more foam dosages are set between the minimum and maximum foam dosages, and foam concrete with 5 foam dosages is prepared, the dry density and thermal conductivity are tested, and the foam dosage is determined; The third step is to determine the amount of recycled powder, prepare foamed concrete according to the determined foam amount and different percentages of recycled powder, test the dry density and compressive strength of the foamed concrete to determine the amount of recycled micro powder and recycled sand powder; the recycled powder is one of recycled micro powder and recycled sand powder; the recycled sand powder is a mixture of sand and powder with a particle size of 0-9.5 mm remaining after the waste concrete is crushed and screened by a jaw crusher to remove coarse aggregates, and is directly used after leaving the factory without treatment; The fourth step is to determine the amount of activator. According to the determined foam content and recycled powder content, the activator content is designed, foam concrete is prepared, and the dry density and compressive strength of foam concrete are measured; the recycled powder content is equal to 40% and the dry density is less than 500kg / m 3 The compressive strength is greater than 0.5MPa and the amount of activator is determined; The fifth step is to weigh the activator according to the determined activator dosage, and place the activator in a beaker and add water to dissolve it: add the activator to the beaker, and the activators in the beaker are sodium hydroxide, sodium carbonate, sodium silicate and sodium sulfate from bottom to top; after the activator is dissolved, pour the dissolved activator into the vertical pure slurry stirring pot; Step 6: weigh the recycled powder according to the determined amount of recycled powder, weigh the sulphoaluminate cement and add them into the vertical pure slurry mixing pot, and stir for two minutes; Step 7: prepare foam in the prepared foam dilution using a foaming machine, weigh the foam according to the determined foam dosage, and freeze the foam at 0 degrees Celsius for 60 seconds; Step 8: Use a scraper to manually stir the cement slurry at the bottom of the vertical slurry stirring pot, add the weighed foam into the cement slurry, and then perform manual stirring and mechanical stirring to complete the preparation of the cement slurry; The ninth step is to cast the prepared cement slurry into shape and demold it after 1-2 days, and then naturally cure it for 28 days.
9. The method for preparing alkali-activated regenerated foamed concrete according to claim 8, characterized in that: The specific steps of manual and mechanical stirring of the cement slurry in the vertical slurry mixing pot in the eighth step are: tilt the vertical slurry mixing pot 45 degrees, stir manually for 5 seconds, put the vertical slurry mixing pot back on the fixed frame, and stir mechanically for 15 seconds; remove the vertical slurry mixing pot, tilt the vertical slurry mixing pot 45 degrees, and stir manually for 30 seconds; put the vertical slurry mixing pot back on the fixed frame, and stir mechanically for 30 seconds.
Citation Information
Patent Citations
Preparation method of high-strength foam concrete heat preservation material
CN105272043A
Full-solid waste cementing material, thermal insulation material, and processing method and application of thermal insulation material
CN109694207A
Foam concrete and preparation method thereof
CN113024179A
High-dosage regenerated sand powder-based foam concrete and a preparation method thereof
CN113429183A
Regenerated foam concrete and preparation method thereof
CN113149580A